Design of Ag-Ge-Zn braze/solder alloys: experimental thermodynamics and surface properties - Delsante, Simona; Li, Dajian; Novakovic, Rada; Borzone, Gabriella (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The experimental investigation of the Ag-Ge-Zn phase diagram was performed by using combined microstructural and Differential Scanning Calorimeter (DSC) analyses. The samples were subjected to thermal cycles by a heat-flux DSC apparatus with heating and cooling rate of 0.5 or 0.3 °C/min. The microstructure of the samples, both after annealing and after DSC analysis, was studied by optical and scanning electron microscopy coupled with EDS (Energy Dispersive Spectroscopy) analysis. Considering the slow heating and cooling rate adopted, the isothermal section at room temperature was established. No ternary compounds were observed. On the basis of the experimental investigations the invariant reactions were identified. Combining the thermodynamic data on the Ag-Ge, Ag-Zn and Ge-Zn liquid phases by means of Butler’s model the surface tension of Ag-Ge-Zn alloys was calculated.